Global Weak Solutions for SQG in Bounded Domains. Issue 11 (30th October 2017) - Constantin, Peter; Nguyen, Huy Quang
Abstract: We prove existence of global weak L 2 solutions of the inviscid SQG equation in bounded domains. © 2017 Wiley Periodicals, Inc.